Death is not the end, being forgotten is - Rawool, Parag; Amrelia, Ali Abbas (17AR01) (New Panvel AIKTC, School of Architecture, 2021)
A few estimation states that 68% of world population would move to urban areas by 2050. Mumbai, a city which is home to more than 1.28 crore people have only 202 cemeteries, crematoria and other places of last rites. A majority of them lack proper security and are poorly maintained. The rapid urbanization of the city, higher fertility rate to death rate ratio and high migration have led to a massive lack of space for burial. It has been reported widely that the city lacks space for the dead. Although, funeral practices are considered sacred. They have seen little to no change in many years. The research focuses on these spaces as a symbol of memorization. Religions which do not recommend memorising the dead have been left out at a preliminary stage. The burial practice is a majorly used practice to memorise the loved ones. The burial spaces take large ground in the city and mostly don$1 (Bt use the spaces full potential. Sometimes, poor designing does cause circulation issues and wastage of space. Also, these spaces are not designed to address the traumatic condition one goes through when they lose their loved one. It is a fact that cemeteries are not designed only for the dead but the living that wishes to visit them. The municipal corporation of Mumbai is planning to solve the demand of new burial ground spaces by proposing new cemeteries in the open spaces available in the outskirts of the city. This creates another issue that people in the city centre would be force to travel many miles just to visit their loved one$1 (Bs grave. It is also important to understand, how ancillary activities and associate spaces can change the image of these spaces by bring up positivity instead of fear. This thesis is a research analysis of funeral practices and activities related to them. It focuses on solving these major issues which are not talked about often. It is aimed to conclude with a solution which can solve the problem of lack of space for dead in mega cities with a sustainable approach. Also, using architecture as a tool to change the perception of these spaces of fear to something positive which can help in the welfare of the public.s
Keywords: Project Reports